CITRA PEREMPUAN DALAM NOVEL “BANDAR” KARYA ZAKY YAMANI (THE IMAGE OF WOMEN IN THE NOVEL “BANDAR” BY ZAKY YAMANI) - Abdul Hamid (Universitas Lambung Mangkurat, 2022)
AbstractThe Image of women in the Novel “Bandar” By Zaky Yamani. This study aims todescribe the image of women in the novel Bandar by Zaky Yamani. This is qualitativeresearch. All activities and interpretations of research results are presented in the form ofdescriptions. This research utilizes an approarch of the sociology of literature. Startingfrom this approach, the researcher takes a picture or image of something linked to women,men, traditions, or even the modern world and others. In a literary work, the image mustbe adjusted to the development of the cultural community. The data in this study are words,sentences and discourse contained in the novel. The data source of this research is thenovel “Bandar” by Zaky Yamani, 299 pages. The data collection technique used is the notetaking technique. Data analysis is related to context (novel content) to discuss the image ofwomen. The results showed that there were three types of women’s images in the novelBandar by Zaky Yamani: (1) women’s image to words their role as individuals: namelywomen who were resfectful, wise, gentle, affectionate, caring, pious, firm, hardworkingand persistent, independent, anxious and worried, angry/ emotional, responsible, cheerful,strong and determined, love, hope, beautiful, and hurt; (2) Women’s image as theirdomestic roles: namely the women as wives who are educating, devoting, to husbands andparents, being loyal to partners, caring for the family, feeling sad and disappointed, beingfriends, and being obedient; and (3) Women’s image of their role as members of thecommunity, namely women who are conducting the renewal, providing entertainment toothers, having a forgiving spirit to others, having a spirit of helping the others, beingbrave, demanding justice, being social, being completed in the cultural traditions of forcedmarriage, oppressed, and giving resistance.Key words: women’s image, individuals, domestic, community, novelAbstrakCitra Perempuan dalam Novel “Bandar” Karya Zaky Yamani. Penelitian ini bertujuanmendeskripsikan citra perempuan dalam novel Bandar Karya Zaky Yamani. Penelitian inimerupakan metode deskriptif kualitatif secara keseluruhan memanfaatkan cara-carapenafsiran dengan menyajikannya dalam bentuk deskripsi. Pendekatan yang digunakandalam penelitian ini adalah sosiologi sastra ialah pendekatan yang mengambil gambaranatau citra tentang sesuatu yang di kaitkan pada perempuan, laki-laki, tradisi, atau pun duniamodern dan lain-lain. Dalam suatu karya sastra citra harus di sesuaikan denganperkembangan budaya masyarakat. Ada pun data dari penelitian ini berupa kata, kalimatdan wacana yang terdapat dalam novel. Sumber data dalam penelitian ini adalah novel“Bandar” Karya Zaky Yamani sebagai novel pertamanya dengan tebal novel 299 halaman.Teknik pengumpulan data yang digunakan dalam penelitian ini adalah teknik catat.Analisis data akan selalu dihubungkan dengan konteks (isi novel) untuk mengetahuipembahasan mengenai citra perempuan. Hasil penelitian menunjukkan bahwa ada tiga citraperempuan dalam novel Bandar Karya Zaky Yaman yaitu (1) Citra perempuan terhadapperannya sebagai individu berupa perempuan yang menghormati, bijaksana/ penyabar,lemah lembut, penyayang, peduli, taqwa, tegas, pekerja keras dan gigih, mandiri, cemasdan khawatir, pemarah/emosi, bertanggung jawab, pengembira, tegar dan teguh, cinta,berharap, cantik, dan sakit hati. (2) Citra perempuan terhadap perannya sebagai domistik(keluarga) berupa perempuan sebagai istri yang mendidik, bakti pada suami dan orang tua,setia pada pasangan, perhatian pada keluarga, merasakan sedih dan kecewa, bersahabatsesama, dan penurut. (3) Citra perempuan terhadap perannya sebagai masyarakat berupaperempuan pembaharuan, menghibur orang lain, berjiwa pemaaf pada orang lain, berjiwapenolong, pemberani, menuntut keadilan, sosial, terperengkap dalam tradisi budaya kawinpaksa, tertindas, dan memberi perlawanan.Kata-kata kunci: citra perempuan, individu, domistik, masyarakat, novel